Inferior Turbinectomy: An Unusual Presentation of Complication of Nasotracheal Intubation - Prasanna, Deepak; Mazumdar, Utpal; Bhat, Sonia; Nigam, Neeraj; Jain, Sandeep (Journal of Orofacial Research, 2012)
This article describes a case of accidental turbinectomy encountered at the time of tracheal intubation while inducing anesthesia at the time of an elective surgery. This is a rare complication in the field of anesthesia with very few reported cases till date. The article highlights the complications which were encountered due to the accidental turbinectomy and thereafter discusses the methods to prevent it.